Teachers’ Experience on Parent-Teacher Collaboration for Students’ Learning - Basnet, Mahendra (Rupantaran: A Multidisciplinary Journal, 2026)
Parent-teacher collaboration is essential for improving students’ learning, motivation, and overall development. However, teachers' lived experiences of this collaboration are not explored in the Nepalese context. This phenomenological qualitative study examines teachers’ experiences of parent-teacher collaboration for students’ learning. It also explores the difficulties and challenges they encounter when working with parents during their teaching journey. This study adopted a qualitative design and applied purposive sampling for selecting secondary-level teachers as participants. An in-depth interview was used to collect data. Based on the research questions, thematic coding and categorisation were done. The findings reveal that teachers' experience of parental engagement involves various practices. However, the study also indicates effective collaboration. In gist, the study highlights parent-teacher collaboration as a complex process that requires flexible, inclusive, and context-sensitive strategies to make a valuable impact among Nepalese schools.